Pengaruh Earning PER Share dan Price Earning Ratio terhadap Price Book Value pada Perusahaan Sektor Pertambangan yang Terdaftar di Indeks IDX30 Tahun 2015-2020 - Kusumawardhani, Aninditha Putri (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
The number of investors who own shares in the mining sector makes an investor must know what ratios can help analyze his chosen stock in order to maximize his investment returns. This study aims to determine the effect of earnings per share and price earnings ratio on price book value, especially in mining sector companies in the IDX30 index year 2015-2020. The method used in this research is descriptive with a quantitative approach. The population and sample of this study are six companies engaged in the mining sector whose shares are listed on the IDX30 index of the Indonesia Stock Exchange. The goal to be achieved in this study is to analyze how the effect of earnings per share and price earnings ratio on the price book value of mining sector companies in the IDX30 index year 2015-2020. The results of this study can be explained that the Sig value of Earning Per Share is of 0.668 or a value of 0.505 <0.05 with a t value of 0.433 so that it can be explained that the level of Earning Per Share has no effect on the price book value. While the Sig of the Price Earning Ratio is 0.578 or the value is 0.578 <0.05. Which means that the high and low Price Earning Ratio has no effect on the price book value. Meanwhile, simultaneously, the value of Sig. 0.758 > 0.05, it means that it can be concluded that simultaneously the Earning Per Share and Price Earning Ratio variables have no significant effect on Price Book Value.